(untitled) (Вестник КазНУ. Серия Востоковедения, 2017)
In this article there were shown Kazakh and English languages of phraseological description of woman appearance. Comparing the descriptions of woman’s beauty appearance which in Kazakh and English languages; in the aesthetical point of view to analyze their differences and similarities. On the fact that both of these nations evolved in different places, have their own history, language, traditions, way of life and economy. Using the phraseological descriptions to compare different nation’s peculiarities from view of lingual-culture and aesthetics.